1974
DOI: 10.1139/y74-120
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization-induced Bone Alterations in Chickens

Abstract: Unilateral wing immobilization was used to study bone changes associated with lack of exercise in young chickens. With disuse, humerus bone weight, diameter, cortical thickness, radiographic density, and breaking strength were reduced significantly, whereas bone length, ash, calcium, and phosphorus were unchanged. The results of this study indicate that exercise-related bone changes can best be shown by radiographic density and breaking strength, but not by bone ash or mineral determinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The reduction of the bone strength is caused by disuse atrophy. This was shown by Nightingale et al (1974) who, by immobilising one wing of broilers, provoked a reduction in the weight and breaking strength of the humerus on that site, compared to the free wing. Rowland and Harms (1972) reported that layers housed in cages from 20 weeks of age showed a significant reduction in bone strength after only 4 weeks, compared to controls on deep litter.…”
Section: Discussionmentioning
confidence: 85%
“…The reduction of the bone strength is caused by disuse atrophy. This was shown by Nightingale et al (1974) who, by immobilising one wing of broilers, provoked a reduction in the weight and breaking strength of the humerus on that site, compared to the free wing. Rowland and Harms (1972) reported that layers housed in cages from 20 weeks of age showed a significant reduction in bone strength after only 4 weeks, compared to controls on deep litter.…”
Section: Discussionmentioning
confidence: 85%
“…However, the thickness of the contralateral pectoralis (not presented) did not differ from that of the controls in our study, suggesting it was not exercised any more than in the non-immobilized birds. Similarly, Nightingale et al [ 68 ] ruled out the presence of hypertrophy of non-immobilized wings in one-wing-splinted broiler chicks, as the humeral density of the non-immobilized wing did not differ from that of the control group. Additionally, no changes were observed in lower leg muscle thickness.…”
Section: Discussionmentioning
confidence: 99%
“…It would have been interesting to investigate changes to the physical bone properties (e.g. bone breaking strength, bone ash content, bone mineral content, bone density) of the keel bone as a result of immobilization [68,[72][73][74], but this was not possible without sacrificing birds. Keel deviations did not change over the experiment and were not common.…”
Section: Discussionmentioning
confidence: 99%
“…A probable cause of the reduced strength of humeri is atrophy of bone tissue due to inactivity. Nightingale et al (1974) observed reduced breaking force, weight, and cortical thickness of humeri from broilers subjected to unilateral wing immobilization when compared with nontaped controls. 'Salaries and research support provided by State and Federal Funds appropriated to the Ohio Agricultural Research and Development Center, The Ohio State University.…”
Section: Introductionmentioning
confidence: 86%